THE INFLUENCE OF LEARNING STYLES AND METACOGNITIVE SKILLS ON STUDENTSâ€™ CRITICAL THINKING IN THE CONTEXT OF STUDENT CREATIVITY PROGRAM - Samsudin, Didin; Hardini, Tri Indri (International Journal of Education, 2019)
Improving studentsâ€™ critical thinking is very important in learning process because one of the goals of critical thinking is to develop students ' critical thinking in the perspective of collectable information. The approach used to address the problem of critical thinking is through learning style and metacognitive skill. The Student Creativity Program is a great way to hone critical thinking at the university level. This research is intended to find out the level of metacognitive skills, learning style, and critical thinking and the influence of metacognitive skills and learning styles among a total of 55 students of a Korean Education Study Program at a state university in Indonesia in the context of Student Creativity Program. This research used survey to find about studentsâ€™ learning styles and their level of metacognitive skill. A test was also conducted to find out the level of studentsâ€™ critical thinking. The data were calculated by the SPSS to test the hypothesis. The research results for learning styles show that 33 (60%) of the students were in the â€œmediumâ€ category and 22 (40%) were in the â€œhighâ€ category, and there was no student categorised into the â€œlowâ€ category. In terms of metacognitive skills, 53 students (98.2%) were in the â€œhighâ€ category and 2 (1.8%) in the â€œmediumâ€ category, and no one was in the â€œlowâ€ category. All students were identified to have â€œhighâ€ level critical thinking. Based on the significance test, there learning style had no significance influence on critical thinking; however, there metacognition skills had significant influence on critical thinking because.